Russia-Ukraine military conflict and imperatives of diversification of Armenia's foreign policy - Vardazaryan, Marut (YSU Journal of International Affairs, 2022)
This article reviews the reasons behind Russia-Ukraine dispute and conducts comparative analysis of this conflict in the context of worldwide geopolitical processes. Ukrainian crisis undermined system of international relations. After the conflict started, the interests of world centers became obvious. This conflict is unfolding in the prism of the US strategy retaining its global dominance and as a result, changing techno-political structure of the world economics. This article also analyzes consequences and challenges of this conflict for the Republic of Armenia and the necessity of diversifying the foreign policy in the new regional reality.
Keywords: Republic of Armenia; Russia; EU; Zbigniew Brzezinski; Henry Kissinger; conflict; global dominance; diversification